(untitled) (Journal of Economic Research & Business Administration, 2024)
The relevance of the development of creative industries, the promotion of the Kazakh creative economy is increasingly gaining its popularity, which is a young, fast-growing economic sector. That is, they are goods and services created through the process of creativity and economic value of society. The creative economy operates on the basis of freedom of expression, interest and motivation of people. However, despite the presence of significant creative and intellectual potential, the process of recognizing human abilities as a full-fledged component of socio-economic formation faces a number of issues, for the solution of which it is necessary to develop new scientific and ideological approaches that correspond not only to modern realities, but also capable of developing in the future. The article covers theoretical issues of the creative economy, examines its basic concepts and global content. The cultural prerequisites for the formation of a creative economy are shown, the issues of its measurement are explored, and the creativity index of regions such as Astana, Almaty and Shymkent is determined. The place of Kazakhstan in the global markets of creative industries is shown, the potential of the cultural heritage sector, creative industries and the market of creative services in Kazakhstan is considered. Mechanisms for supporting creative industries are outlined. The purpose of the study of the creative economy is to create an attractive investment climate, modernize the sphere of education, science, tourism and other economic issues of modern society. As a result of the study of the issues of the creative economy, conclusions and proposals were made for the further successful development of the new economy, where creativity becomes the most important factor in the formation of a modern way of life and the prosperity of the economy. Key words: creative economy, innovative services, investment climate, start-up industries, creative product.